Management of retropharyngeal lymph node metastasis in oral cancer. (December 2019) - Oikawa, Yu; Michi, Yasuyuki; Tsushima, Fumihiko; Tomioka, Hirofumi; Mochizuki, Yumi; Kugimoto, Takuma; Osako, Toshimitsu; Nojima, Hitomi; Yokokawa, Misaki; Kashima, Yoshihisa; Harada, Hiroyuki
Highlights: Retropharyngeal lymph node (RPLN) metastasis is extremely rare in oral cancer. RPLN metastasis had poorer prognosis than cervical lymph node metastasis. Early detection and surgical excision improve the prognosis of RPLN in oral cancer. Abstract: Objectives: Retropharyngeal lymph node (RPLN) metastasis is extremely rare, and prognosis is significantly poor in oral cancer. We retrospectively examined the management of RPLN metastases in oral cancer. Materials and methods: A total of 1247 patients with oral cancer were treated at our department from January 2002 and December 2016. Among these patients, 374 (30%) had histologically positive lymph node metastases. Of these, 15 patients (1.2%) were diagnosed with RPLN metastases. We evaluated the diagnostic period, size, recurrence pattern, laterality, treatment, and therapeutic outcomes. The Kaplan–Meier method was used to determine overall survival (OS) among the RPLN metastasis group, cervical lymph node (CLN) metastases group, and treatment methods group for RPLN metastases. Results: One patient had RPLN involvement at the initial treatment, and RPLN involvement in other patients was found subsequently. The mean duration in confirming RPLN metastases was 228 days (range, 50–867 days). Surgical therapy was performed in 5 patients, chemoradiotherapy in 7 patients, and best supported care (BSC) in 3 patients. The cumulative 5-year OS rate for the RPLN metastasis group (n = 15) was 38.1%, compared with the rate of 71.3% for the CLN group (n = 359). Regarding the therapeutic approach for RPLN metastases, OS rates were 80.0% (n = 5) in the surgical therapy group, 28.6% (n = 7) in the chemoradiotherapy group, and 0% (n = 3) in the BSC group. Conclusion: Early detection and surgical treatment of RPLN metastases are associated with increased survival rate in oral cancer.